Characterization of NTC thick film thermistor paste Cu0.2Ni0.5Zn1.0Mn1.3O4 - Aleksić Stanko O.; Obradović Nina N.; Mitrović Nebojša S.; Luković Miloljub D. (Science of Sintering, 2024)
A powder of Cu0.2Ni0.5Zn1.0 Mn1.3O4 composition for custom thermistor was prepared by using the respective mixture of metal oxides and solid state reaction at 1000 °C/4h in air. The obtained thermistor powder was milled in the planetary ball mill and agate mill for a prolonged time to achieve submicron powder. The prepared thermistor powder was further characterized by using XRD and SEM techniques. After that, the thermistor powder was pressed into small disc-shaped samples and sintered at 1150°C/2h. The sintered samples were also characterized by using XRD and SEM. The main electrical properties such as nominal resistance R and thermistor exponential factor B were measured in the climatic test chamber. After that, the thick film paste was prepared using the same powder, an organic vehicle and a glass frit. The paste was printed on alumina substrate, dried at 150 =°C /30 min and sintered in air at 850°C /10 min in a hybrid conveyor furnace. Planar electrodes were printed on the sintered NTC thermistor layer using PdAg thick film paste. The electric properties of the sintered thick film thermistor were also measured in the climatic test chamber. The obtained results were used for development of novel self-heating thermistor applications.